Integration of Environmental Stewardship Issues in Islamic Education Curriculum: an Ecotheological Review with a Humanist Paradigm - Rofiqotul Aini; Muhlisin; Moh. Sugeng Sholehuddin; Fatah Syukur; Muhammad Fikri bin Zubaidi (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
Various challenges arising from globalization and the ecological crisis confront Islamic education in the modern era. These conditions have raised fundamental concerns about the relevance of the Islamic education curriculum, which tends to remain normative and textual in orientation, exhibits limited integration of ecological values, and is insufficiently responsive to contemporary humanitarian and global environmental issues. This article aims to analyze the integration of Islamic education curriculum with environmental stewardship issue based on ecotheology within humanist paradigm. This study used a library research method with a Systematic Literature Review (SLR) approach. The review followed the PRISMA 2020 guidelines to systematically identify, screen, assess, and select relevant literature from scholarly books and articles in journals with keys the Islamic education curriculum, ecotheology, environmental stewardship, and humanist paradigm. The selected literature was analyzed using content analysis to identify, interpret, and synthesize the principal themes and key findings. The findings indicate that integrating environmental stewardship issues into the Islamic curriculum through the implementation of ecotheological values, such as tauhid, khalīfah fil ard, amanah, tawazun, and Islam rahmatan lil alamin, can foster Islamic education curriculum that is adaptive, contextual, and future-oriented. Furthermore, this study confirms that curriculum design integrating ecotheological values within a humanistic paradigm significantly strengthens faith-based ecological awareness, develops humanistic character, and internalizes sustainability values in students' behavior.